2016
DOI: 10.3892/ol.2016.4881
|View full text |Cite
|
Sign up to set email alerts
|

miR-19a/b modulates lung cancer cells metastasis through suppression of MXD1 expression

Abstract: Abstract.Increasing evidence has shown that microRNA (miRNA) is extensively involved in the pathophysiology of lung cancer. Microarray data demonstrated the increasing levels of miR-19a in the peripheral blood from patients suffering from lung cancer, which is closely associated with poor prognosis of lung cancer. However, the underlying molecular mechanism of miR-19a remains to be determined. The results of the present study showed a higher expression of miR-19a compared with normal bronchial epithelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…MXD1 was reported to have inhibitory functions in various cancers such as breast cancer 26 and lung cancer 27 . In this study, MXD1 was identified as a downstream target of miR‐525‐5p.…”
Section: Discussionmentioning
confidence: 79%
“…MXD1 was reported to have inhibitory functions in various cancers such as breast cancer 26 and lung cancer 27 . In this study, MXD1 was identified as a downstream target of miR‐525‐5p.…”
Section: Discussionmentioning
confidence: 79%
“…Increasing evidence has shown that more than half of miRNA genes are located at fragile sites (12)(13)(14). Several studies reported that numerous miRNAs are aberrantly expressed in various human cancers and play significant roles in tumourigenesis and tumour development, including NSCLC (15)(16)(17). Obviously, miRNAs can function as either tumour suppressors or oncogenes in different human cancers depending on the characteristics of their target genes (18).…”
Section: Introductionmentioning
confidence: 99%
“…MiR-19a promoted proliferation and metastasis of lung cancer cells by targeting MAX dimerization protein 1 (MXD1). 28 It is clear that miR-19a promotes cancer occurrence and development. However, the role of miR-19a in CSCs, especially in the OS stem cells, remains unclear.…”
Section: Discussionmentioning
confidence: 99%